Distributed discharge and sediment concentration predictions in the sub‐humid Ethiopian highlands: the Debre Mawi watershed. Issue 7 (28th August 2014) - Tilahun, Seifu A.; Guzman, Christian D.; Zegeye, Assefa D.; Dagnew, Dessalegn C.; Collick, Amy S.; Yitaferu, Birru; Steenhuis, Tammo S.
Abstract Experimental research in the Ethiopian highlands found that saturation excess induced runoff and erosion are common in the sub‐humid conditions. Because most erosion simulation models applied in the highlands are based on infiltration excess, we, as an alternative, developed the Parameter Efficient Distributed (PED) model, which can simulate water and sediment fluxes in landscapes with saturation excess runoff. The PED model has previously only been tested at the outlet of a watershed and not for distributed runoff and sediment concentration within the watershed. In this study, we compare the distributed storm runoff and sediment concentration of the PED model against collected data in the 95‐ha Debre Mawi watershed and three of its nested sub‐watersheds for the 2010 and 2011 rainy seasons. In the PED model framework, the hydrology of the watershed is divided between infiltrating and runoff zones, with erosion only taking place from two surface runoff zones. Daily storm runoff and sediment concentration values, ranging from 0.5 to over 30 mm and from 0.1 to 35 g l−1, respectively, were well simulated. The Nash Sutcliffe efficiency values for the daily storm runoff for outlet and sub‐watersheds ranged from 0.66 to 0.82, and the Nash–Sutcliffe efficiency for daily sediment concentrations were greater than 0.78. Furthermore, the model uses realistic fractional areas for surface and subsurface flow contributions, for example between saturated areas (15%), degraded areas (30%) and permeable areas (55%) at the main outlet, while close similarity was found for the remaining hydrology and erosion parameter values. One exception occurred for the distinctly greater transport limited parameter at the actively gullying lower part of the watershed. The results suggest that the model based on saturation excess provides a good representation of the observed spatially distributed runoff and sediment concentrations within a watershed by modelling the bottom lands (as opposed to the uplands) as the dominant contributor of the runoff and sediment load. Copyright © 2014 John Wiley & Sons, Ltd.